Investment Effects of Wealth Taxes under Uncertainty and Irreversibility - Rainer Niemann; Caren Sureth-Sloane (Center for Economic Studies and ifo Institute (CESifo), 2015)
The growing dissatisfaction with perceived distributional inequality and budgetary constraints gave rise to a discussion on the (re-)introduction of wealth taxes. Wealth taxes are typically levied on private wealth, in some countries also on corporate wealth. To avoid misleading statements concerning possible distributional consequences of wealth taxes, preceding analyses of the economic and particularly investment effects are necessary. As investments drive job creation, tax-induced changes in investment timing may significantly affect the income and wealth distribution. We analyze the impact of wealth taxes on investment timing under uncertainty and irreversibility and the propensity to carry out risky projects. Using a Dixit/Pindyck type real options model we find that wealth taxes have real effects. This means that higher wealth tax rates can either stimulate or depress the propensity to invest in risky projects. We find that apparently paradoxical wealth tax effects (accelerated investment due to higher wealth tax rates) are more likely for low interest rates and for high-risk investments. Using either historical cost or fair value accounting may affect investment timing ambiguously. Thus, the design of wealth taxes is crucial for the resulting delay or acceleration of investment. Although our model takes an individual perspective, our findings are also relevant for the current tax policy discussion on the introduction of wealth taxes. Our results indicate that wealth taxes are particularly harmful for specific classes of investments, for example low-risk investments.
Keywords: H21; H25; 330; wealth tax; investment decisions; real options; timing flexibility; uncertainty; irreversibility